Self-defense devices in the performative work of Ana Flávia Cavalcanti (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article sought to deepen the notion of a self-defense dispositive based on the analysis of Brazilian artist Ana Flávia Cavalcanti’s performative work Pau no Rabo (2021). We start from Elsa Dorlin's theoretical support on the theme of self-defense and, based on the foundations offered by Cavalcanti's performance, we seek to raise questions about the concept of male gaze elaborated by Laura Mulvey, in addition to investigating performative practices that highlight gender violence. The text also sought to analyze other artistic works that address the representation of women in public space, regarding walking and occupying the streets as gestures of self-defense, suggesting a dimension of insurrection and uprising bodies.
Keywords: performance; self-defense; male gaze; Elsa Dorlin; Ana Flávia Cavalcanti